Simultaneous Determination of Amlodipine, Hydrochlorothiazide, and Valsartan in Pharmaceutical Products by a Combination of Full Spectrum Measurement and Kalman Filter Algorithm - Nguyen Thi Quynh Trang; Nguyen Van Hop; Nguyen Dang Giang Chau; Thuc Binh Tran (Advances in Materials Science and Engineering)
In this work, a new solution has been found for selecting the approximate initial value of concentration (by means of the classical least squares) and variance (calculated by the Horwitz equation) for the Kalman filter algorithm. With this solution, the Kalman method is less error-prone and has a better repeatability than the least squares method when using the full spectrum. A protocol for simultaneous determination of amlodipine (AML), hydrochlorothiazide (HYD), and valsartan (VAL) in pharmaceutical products was developed based on the spectrophotometry-chemometric method using full spectrum measurement in combination with the Kalman filter algorithm written in Microsoft Excel 2016 and Visual Basic for Applications (VBA). The method was validated on the Exforge HCT tablets with good repeatability (RSD) (varied from 2.2% to 2.3% (n = 3) for all the three studied compounds) and good recovery (90.0%–94.0% for AML, 90.3%–94.5% for HYD, and 98.5%–103.1% for VAL (n = 3)). The results were in good agreement with the measurements achieved from the high-performance liquid chromatography (HPLC) method.